Early Frontal qEEG Markers Predict Delayed Cognitive Recovery After Mild-to-Moderate Ischemic Stroke: A Prospective Cohort Study - Vy Tuong Nguyen; Trang Ho Thu Quach; Hiep Do; Kien Trung Duong; Khoa Nhat Bui; An Gia Pham; Huong Ha; Thang Cong Tran (Clinical EEG and Neuroscience, 2026)
Background and Objective Post-stroke cognitive impairment affects 30%–60% of survivors, yet predicting which patients will demonstrate delayed recovery remains challenging. We investigated whether early quantitative electroencephalography (qEEG) markers can identify patients with cognitive recovery potential during the critical 3–6 month post-stroke period. Methods This prospective cohort study enrolled patients with first-time supratentorial ischemic stroke (NIHSS